Psychological Capital Relates With Teacher Enjoyment: The Mediating Role of Reappraisal - Zhou, Xiang; Zheng, Songyun (Frontiers in Psychology, 2022)
This study examined the relationship between psychological capital (PsyCap) and teacher enjoyment in the context of online teaching and investigated whether the emotion regulation (ER) strategy of reappraisal mediated their relationship. 221 Chinese university teachers were selected as the research sample through snowball sampling in an online survey. After controlling for age, gender, teaching experience, education level, time and energy input during online teaching and online teaching experience, the results showed that PsyCap and reappraisal positively influence the teachers’ online teaching enjoyment (OTE), and reappraisal significantly mediated the relationship between teachers’ PsyCap and OTE, suggesting that optimistic and resilient teachers with more self-efficacy and hope are more likely to find enjoyment during online teaching, and high PsyCap combined with the use of reappraisal leads to greater OTE. The study not only confirms the positive role of reappraisal as an emotion regulation strategy in online teaching, but also provides practical implications for the realization of enjoyable online teaching experience. Keywords: psychological capital, reappraisal, teaching enjoyment, emotion regulation, online teaching